A Sequence-Ready Physical Map of Barley Anchored Genetically by Two Million Single-Nucleotide Polymorphisms . Issue 1 (15th November 2013) - Ariyadasa, Ruvini; Mascher, Martin; Nussbaumer, Thomas; Schulte, Daniela; Frenkel, Zeev; Poursarebani, Naser; Zhou, Ruonan; Steuernagel, Burkhard; Gundlach, Heidrun; Taudien, Stefan; Felder, Marius; Platzer, Matthias; et al.
Abstract : A genome-wide physical map of barley was constructed and anchored genetically by a novel method involving whole-genome resequencing of a mapping population . Abstract: Barley ( Hordeum vulgare ) is an important cereal crop and a model species for Triticeae genomics. To lay the foundation for hierarchical map-based sequencing, a genome-wide physical map of its large and complex 5.1 billion-bp genome was constructed by high-information content fingerprinting of almost 600, 000 bacterial artificial chromosomes representing 14-fold haploid genome coverage. The resultant physical map comprises 9, 265 contigs with a cumulative size of 4.9 Gb representing 96% of the physical length of the barley genome. The reliability of the map was verified through extensive genetic marker information and the analysis of topological networks of clone overlaps. A minimum tiling path of 66, 772 minimally overlapping clones was defined that will serve as a template for hierarchical clone-by-clone map-based shotgun sequencing. We integrated whole-genome shotgun sequence data from the individuals of two mapping populations with published bacterial artificial chromosome survey sequence information to genetically anchor the physical map. This novel approach in combination with the comprehensive whole-genome shotgun sequence data sets allowed us to independently validate and improve a previously reported physical and genetic framework. The resources developed in this study will underpin fine-mapping and cloning of agronomically important genes and the assembly of a draft genome sequence.